Extracellular glutamate is not modulated by cannabinoid receptor activity - Delia N. Chiu; Brett C. Carter (Scientific Reports)
Abstract Cannabinoid receptor activation has been proposed to trigger glutamate release from astrocytes located in cortical layer 2/3. Here, we measure the basal concentration of extracellular glutamate in layer 2/3 of mouse somatosensory cortex and find it to be 20–30 nM. We further examine the effect of cannabinoid receptor signaling on extracellular glutamate, and find no evidence for increased extracellular glutamate upon cannabinoid receptor agonist application.